LITERATURE REVIEW: MONOCLONAL ANTIBODY THERAPY FOR MIGRAINE - Owen Johanes Maliangkay; Timothy L. Batasina; Ferrdy Pratama Wijaya; Theresia Runtuwene; Arthur H.P. Mawuntu (Jurnal Sinaps, 2021)
Migraine headaches are one of the most frequent types of primary headaches, and they can be difficult to treat. Pharmacological and non-pharmacological therapy, as well as abortive and preventative therapy, are all options for treatment. Calcitonin Gene-Related Peptide (CGRP) plays a key role in migraine pathophysiology and is now being employed as an abortive and preventive treatment. CGRP antagonist therapy and monoclonal antibodies (MAB) are two types of therapy that block the CGRP pathway. So far, four MAB treatments for migraine have shown promise. Clinicians should be familiar with MAB therapy for migraine since it is likely to become a popular treatment option in the future.